δ-Cells: The Neighborhood Watch in the Islet Community - Rui Gao; Tao Yang; Quan Zhang (Biology, 2021)
Somatostatin-secreting δ-cells have aroused great attention due to their powerful roles in coordination of islet insulin and glucagon secretion and maintenance of glucose homeostasis. δ-cells exhibit neuron-like morphology with projections which enable pan-islet somatostatin paracrine regulation despite their scarcity in the islets. The expression of a range of hormone and neurotransmitter receptors allows δ-cells to integrate paracrine, endocrine, neural and nutritional inputs, and provide rapid and precise feedback modulations on glucagon and insulin secretion from α- and β-cells, respectively. Interestingly, the paracrine tone of δ-cells can be effectively modified in response to factors released by neighboring cells in this interactive communication, such as insulin, urocortin 3 and γ-aminobutyric acid from β-cells, glucagon, glutamate and glucagon-like peptide-1 from α-cells. In the setting of diabetes, defects in δ-cell function lead to suboptimal insulin and glucagon outputs and lift the glycemic set-point. The interaction of δ-cells and non-δ-cells also becomes defective in diabetes, with reduces paracrine feedback to β-cells to exacerbate hyperglycemia or enhanced inhibition of α-cells, disabling counter-regulation, to cause hypoglycemia. Thus, it is possible to restore/optimize islet function in diabetes targeting somatostatin signaling, which could open novel avenues for the development of effective diabetic treatments.